2018
DOI: 10.18353/crustacea.47.0_5
|View full text |Cite
|
Sign up to set email alerts
|

<i>Ceratothoa verrucosa</i> (Isopoda: Cymothoidae) attached by <i>Choricotyle elongata</i> (Platyhelminthes: Monogenea) in the mouth cavity of red seabream <i>Pagrus major</i>

Abstract: Abstract. Over more than one century since 1894, cymothoid isopods attached by the diclidophorid monogenean Choricotyle elongata (Goto, 1894) in the mouth cavity of Japanese sparids have not been exactly identified. This note reports that those isopods are identifiable as Ceratothoa verrucosa (Schioedte & Meinert, 1883) based on material of the species attached by Ch. elongata in the mouth cavity of a red seabream, Pagrus major (Temminck & Schlegel, 1843), from the Seto Inland Sea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It was possible that these isopods were actually C. verrucosa, as this species is the only confirmed isopod parasite of these two sparids (Yamauchi, 2016). Later, Nagasawa and Nitta (2018) observed that C. verrucosa in the mouth cavity of red seabream was attached by Ch. elongata.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible that these isopods were actually C. verrucosa, as this species is the only confirmed isopod parasite of these two sparids (Yamauchi, 2016). Later, Nagasawa and Nitta (2018) observed that C. verrucosa in the mouth cavity of red seabream was attached by Ch. elongata.…”
Section: Discussionmentioning
confidence: 99%